Clinical aspects and antenatal diagnosis of invasive placenta: a review of ten-years’ experience of a multi-profile hospital in Lithuania - Volochovič, Jelena; Ramašauskaitė, Diana; Šimkevičiūtė, Ramunė (Acta medica Lituanica, 2017)
Background. Invasive placenta is a rare obstetrical pathology that is life-threatening to mother and child. It is important to diagnose this pathology as early as possible and to plan further optimal care of patients in order to minimize life-threatening complications. The aim of this study was to analyze the frequency of cases of invasive placenta, the peculiarities of their clinical manifestation in women who gave birth from 2006 to 2015, to evaluate diagnostic and treatment options of this pathology, and to review their changes when the level of services provided by the institution changes. Materials and methods. A retrospective study was performed of the ten-year period of 2006 to 2015. The study consisted of examining the data of medical records of a group of 14 women. Results. The incidence of invasive placenta at the secondary level hospital was 1/2170 births, 1:934 births at the tertiary level. There were only three patients (21.4%) diagnosed with invasive placenta during pregnancy at Vilnius University Hospital Santaros Klinikos Obstetrics and Gynaecology Centre. Before the surgery, pre-occlusive balloons were ushered into the internal iliac artery and inflated to reduce bleeding after the newborn delivery. The amount of blood loss in the whole group ranged from 1000 to 6500 ml (avg. 3130.7 ml). Radical treatment was given to eleven patients. Conclusion. Invasive placenta is a life-threatening condition. Tertiary-level hospitals have a greater capacity for antenatal diagnostics. Timely diagnosis of placental invasion and evaluation of the level of the myometrium damage before delivery is instrumental in planning patient care and preparing for delivery and operation.